Assessing the Quality of Available Patient Reported Outcome Measures for Intermittent Claudication: A Systematic Review Using the COSMIN Checklist. Issue 3 (March 2015) - Conijn, A.P.; Jens, S.; Terwee, C.B.; Breek, J.C.; Koelemay, M.J.W.
Abstract : Objective: The aim was to critically appraise, compare, and summarize the quality of the measurement properties of all available disease specific patient reported outcome measures (PROMs) on health related quality of life and functional status validated in patients with intermittent claudication (IC). Methods: A systematic search was carried out in Embase and Medline (last search November 18, 2013). The quality of the identified studies was assessed per measurement property according to the COnsensus-based Standards for the selection of health Measurements Instruments (COSMIN) checklist. Data on the measurement properties were extracted to determine a level of evidence per measurement property per instrument. Results: Forty three studies were found evaluating 10 health related quality of life and two functional status PROMs. Evidence for the existence of subscales (structural validity) and for internal consistency (interrelatedness of items within subscales) for PROMs was generally poor. Evidence for construct validity was limited. Accuracy and reproducibility of PROMs were often uncertain, since reliability studies were mostly performed in small patient samples. Responsiveness, or the ability of PROMs to detect change over time, was hardly ever studied. Conclusion: The quality of the validation of most disease specific PROMs for IC is alarming, hampering all conclusion based on these PROMs. Considering the results, the PAD quality of life questionnaire (PADQOL), Intermittent claudication questionnaire (ICQ) and the Vascular quality of life questionnaire (VascuQol) might be appropriate PROMs for health related quality of life, while the Walking impairment questionnaire (WIQ) and Estimate ambulation capacity by history questionnaire (EACH-Q) appear suitable PROMs for functional status. However, all PROMs require further validation studies to fill the gaps in their measurement properties. The shortcomings highlighted in this review should be taken into account when interpreting PROM results.